2022
DOI: 10.3390/ijms23158761
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glutamine Uptake Resensitizes Paclitaxel Resistance in SKOV3-TR Ovarian Cancer Cell via mTORC1/S6K Signaling Pathway

Abstract: Ovarian cancer is a carcinoma that affects women and that has a high mortality rate. Overcoming paclitaxel resistance is important for clinical application. However, the effect of amino acid metabolism regulation on paclitaxel-resistant ovarian cancer is still unknown. In this study, the effect of an amino acid-deprived condition on paclitaxel resistance in paclitaxel-resistant SKOV3-TR cells was analyzed. We analyzed the cell viability of SKOV3-TR in culture conditions in which each of the 20 amino acids were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Chemotherapy resistance remains a critical factor in therapeutic failures among patients with EOC. Amino acid metabolism reprogramming sustains stem cell-like characteristics and drug resistance in EOC cells [ 40 , 41 ]. Notably, our findings indicate that CBR-5884 reduced tumorsphere formation ability and CD44 expression levels, suggesting a decrease in the stemness of OC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy resistance remains a critical factor in therapeutic failures among patients with EOC. Amino acid metabolism reprogramming sustains stem cell-like characteristics and drug resistance in EOC cells [ 40 , 41 ]. Notably, our findings indicate that CBR-5884 reduced tumorsphere formation ability and CD44 expression levels, suggesting a decrease in the stemness of OC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous blocking of glutaminase by CB-839, and of Gln import with V-9302, has shown synergistic effects in hepatocellular carcinomas [ 15 ]. The same ASCT2 transporter inhibitor has also been successfully used to resensitise Paclitaxel-resistant ovarian cancer cells [ 46 ]. Targeting glutaminase with CB-839 has also shown synergy with Bruton tyrosine kinase inhibition in ibrutinib-resistant mantle B-cell lymphoma cells [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we confirmed the upregulation of serine and glycine metabolism affecting paclitaxel resistance in ES2 cells compared to parental cells. A recent study revealed that arginine and glutamine conditions could target amino acid metabolism to suppress survival in ovarian cancer, independent of paclitaxel resistance [42]. Although glutamine deprivation-induced cytotoxicity was reported, little is known about the effects of the serine-glycine metabolic pathway on paclitaxel resistance in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%